2014
DOI: 10.1371/journal.pone.0097041
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Psychiatric Disorders following Polycystic Ovary Syndrome: A Nationwide Population-Based Cohort Study

Abstract: BackgroundPolycystic ovary syndrome (PCOS) is one of the most common endocrine disorders among women of reproductive age. A higher prevalence of psychiatric comorbidities, including depressive disorder, anxiety disorder, and bipolar disorder has been proved in patients with PCOS. However, a clear temporal causal relationship between PCOS and psychiatric disorders has not been well established.ObjectiveWe explored the relationship between PCOS and the subsequent development of psychiatric disorders including sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
92
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 35 publications
(39 reference statements)
6
92
2
3
Order By: Relevance
“…The discrepancy between 1.4% patients diagnosed with depression and 16.3% patients treated with antidepressants could be explained by the fact that many patients are treated for depression by their own general practitioner and only hospital diagnoses are included in NPR. The present data support a moderately increased risk of depression in PCOS and are in agreement with recent studies (2,20,39). In contrast, some studies reported an up to eightfold increased risk of depression in PCOS (18), but treatment with antidepressants is only indicated in moderate or severe and psychotherapy should be used in patients with milder symptoms.…”
Section: European Journal Of Endocrinologysupporting
confidence: 92%
See 1 more Smart Citation
“…The discrepancy between 1.4% patients diagnosed with depression and 16.3% patients treated with antidepressants could be explained by the fact that many patients are treated for depression by their own general practitioner and only hospital diagnoses are included in NPR. The present data support a moderately increased risk of depression in PCOS and are in agreement with recent studies (2,20,39). In contrast, some studies reported an up to eightfold increased risk of depression in PCOS (18), but treatment with antidepressants is only indicated in moderate or severe and psychotherapy should be used in patients with milder symptoms.…”
Section: European Journal Of Endocrinologysupporting
confidence: 92%
“…These results are supported by a recent register-based Taiwanese study reporting a hazard ratio of 1.4 for anxiety disorders in PCOS (39). Anxiety could be associated with depression and low quality of life in PCOS, but more studies are needed to test this hypothesis.…”
Section: European Journal Of Endocrinologysupporting
confidence: 60%
“…The use of anxiety medicine was higher in patients with PCOS compared with controls (7) and in a Taiwanese register-based study, the hazard ratio was 1.4 for anxiety disorders in PCOS (115). Anxiety could be associated with depression and low quality of life in PCOS, but more studies are needed to test this hypothesis.…”
Section: Depression and Psychiatric Illnessmentioning
confidence: 99%
“…The characteristic clinical manifestation of this disease is its high heterogeneity, including high androgen, insulin resistance (IR) and glucose metabolism levels, thus the diagnosis and treatment remains difficult. PCOS at the childbearing age is the continuation of adolescent PCOS, which can increase the risks of cardiovascular system and glucose metabolism abnormalities in old age, as well as resulting in disorders of psychological and social cognition functions (2)(3)(4)(5)(6)(7). Therefore, the effective treatment of adolescent PCOS is of particular importance (8).…”
Section: Introductionmentioning
confidence: 99%